2016
DOI: 10.4143/crt.2015.398
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Changes of Quality of Life in Long-Term Survivors after Gastrectomy for Gastric Cancer

Abstract: PurposeA few studies have prospectively evaluated changes in quality of life (QoL) after surgery in short-term survivors; however, no prospective study has evaluated the longitudinal changes in QoL in long-terms survivors. We prospectively evaluated the chronological changes in QoL after a gastrectomy over a 5-year postoperative period in a large group of patients.Materials and MethodsQoL data from the European Organization for Research and Treatment of Cancer QLQ-C30 and the QLQ-STO22 questionnaires were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 19 publications
(31 reference statements)
10
59
0
Order By: Relevance
“…The present study demonstrated that the percent changes from the baseline BMD were − 4.03% in the first postoperative year and − 0.96% in the second postoperative year. Previous studies reported that food consumption decreases in the first postoperative year and gradually improves subsequently [25][26][27]. Our study suggested that reduced food consumption in the early postgastrectomy period strongly affected the BMD, which decreased by 4% in year 1 after surgery.…”
Section: Discussionsupporting
confidence: 48%
“…The present study demonstrated that the percent changes from the baseline BMD were − 4.03% in the first postoperative year and − 0.96% in the second postoperative year. Previous studies reported that food consumption decreases in the first postoperative year and gradually improves subsequently [25][26][27]. Our study suggested that reduced food consumption in the early postgastrectomy period strongly affected the BMD, which decreased by 4% in year 1 after surgery.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, surgery and postsurgery complications result in a significant deterioration in their HRQoL . Moreover, this can be reinforced by the fact that patients are not sufficiently informed about the impact of surgery and the long‐term changes in HRQoL . Several mediators or moderators could improve the current understanding of the role of EC in the HRQoL of these patients after surgery.…”
Section: Discussion‐conclusionmentioning
confidence: 99%
“…Although surgery is the standard curative treatment, it is among those that most affect quality of life and lead to distress . Surgery tends to cause a major deterioration in patients' health‐related quality of life (HRQoL) with a slow and long recovery . Between the presurgery and postsurgery stages, although patients report a stabilization of their anxiety level, they generally experience an increase in their depression symptoms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognosis is extremely poor, even in OECD countries such as the UK, where around 55% of patients die within one year of diagnosis . Those who survive suffer a marked reduction in their quality of life during treatment and recovery . Inflammation is a well‐established risk factor for cancer, and various mechanisms have been proposed to explain this connection .…”
mentioning
confidence: 99%